2008
DOI: 10.1111/j.1365-2621.2007.01555.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study on antioxidative activity of yellow stripe trevally protein hydrolysate produced from Alcalase and Flavourzyme

Abstract: Antioxidative activities of protein hydrolysates from yellow stripe trevally (Selaroides leptolepis) prepared using Alcalase 2.4 L (HA) and Flavourzyme 500 L (HF) with the degree of hydrolysis of 15% by pH-stat method were determined. Both protein hydrolysates exhibited the antioxidative activity in a concentration dependent manner. HF generally showed the greater antioxidative activity than HA (P < 0.05) as indicated by the higher 2,2-diphenyl-1-picryhydrazyl (DPPH) radical scavenging activity, reducing power… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
78
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 107 publications
(86 citation statements)
references
References 29 publications
8
78
0
Order By: Relevance
“…Therefore, chelation of metal ions by peptides in hydrolysates would retard the oxidative reaction (Klompong et al 2008). Ferrous chelating activity has been reported for hydrolysate of silver carp (Hypophthalmichthys molitrix) (Dong et al 2008), round scad (Thiansilakul et al 2007a) and yellow stripe trevally (Klompong et al 2008). In fact, chelating activity of SPHs was higher than that of Flavourzymehydrolyzed silver carp protein which is 60% at 5 mg/ml (Dong et al 2008).…”
Section: Ferrous Ion-chelating Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, chelation of metal ions by peptides in hydrolysates would retard the oxidative reaction (Klompong et al 2008). Ferrous chelating activity has been reported for hydrolysate of silver carp (Hypophthalmichthys molitrix) (Dong et al 2008), round scad (Thiansilakul et al 2007a) and yellow stripe trevally (Klompong et al 2008). In fact, chelating activity of SPHs was higher than that of Flavourzymehydrolyzed silver carp protein which is 60% at 5 mg/ml (Dong et al 2008).…”
Section: Ferrous Ion-chelating Activitymentioning
confidence: 99%
“…For example, at 0.25 mg/ml, the metal chelating activities of EDTA, SPHEE, SPHA1 and SPHA21 were 100%, 78%, 54.82% and 61.58% respectively. Therefore, chelation of metal ions by peptides in hydrolysates would retard the oxidative reaction (Klompong et al 2008). Ferrous chelating activity has been reported for hydrolysate of silver carp (Hypophthalmichthys molitrix) (Dong et al 2008), round scad (Thiansilakul et al 2007a) and yellow stripe trevally (Klompong et al 2008).…”
Section: Ferrous Ion-chelating Activitymentioning
confidence: 99%
“…Thiansalkul et al [20] reported that for the same degree of hydrolysis, FPH prepared using Flavourzyme (a mixture of endo-and exo-peptidase) exhibited higher radical scavenging ability and reducing power, but lower metal chelating ability compared to FPH prepared using Alcalase (an endopeptidase). In a similar study, Klompong et al [21] determined that in yellow stripe trevally, FPH made using Flavourzyme were more antioxidative than those of Alcalase, indicated by higher DPPH radical scavenging ability, reducing power, and metal chelating ability. While studying tilapia FPH, Raghavan et al [22] compared the antioxidant properties of different enzymes and found that hydrolysates prepared using Cryotin (a mixture of trypsin, chymotrypsin, and elastase) showed higher antioxidant activity in washed muscle systems, while hydrolysates prepared using Flavourzyme showed higher 2,2 diphenylpicrylhydrazyl (DPPH) radical scavenging ability (Figs 41.1 and 41.2).…”
Section: Effect Of Enzymes On Antioxidative Activitymentioning
confidence: 99%
“…Readers should exercise caution not to interpret the antioxidant property of FPH in terms of TBARS assay alone, but use the information along with other relevant antioxidant assays [34]. While studying liposomal systems, Klompong et al [21] determined that protein hydrolysates at 200 ppm from the fish yellow stripe trevally significantly inhibited the formation of TBARS. Je et al [35] showed that FPH from the frames of Alaska pollock exhibited antioxidative activity in linoleic acid model system.…”
Section: Inhibition Of Primary and Secondary Lipid Oxidation Productsmentioning
confidence: 99%
See 1 more Smart Citation